THIRD UPDATE ON COMPOUNDS WITH KRöHNKITE-TYPE CHAINS: THE CRYSTAL STRUCTURE OF WENDWILSONITE [CA2MG(ASO4)2 ·2H2O] AND THE NEW TRICLINIC STRUCTURE TYPES OF SYNTHETIC AGSC(CRO4)2·2H2O AND M2CU(CR2O7)2·2 H2O (M = RB, CS) - Kolitsch U.; Fleck M. (My University, 2006)
As part of a comprehensive crystal-chemical study and classification of minerals and synthetic compounds with kröhnkite-type or -like chains of octahedra bridged by tetrahedra, the crystal structures of wendwilsonite from Schneeberg, Saxony, Germany, with composition Ca2(Mg0.90,Co0.10)(AsO4) 2·2H2O, and of three new synthetic double-metal dichromate(VI) dihydrates have been determined from single-crystal X-ray diffraction data. Wendwilsonite is monoclinic [space group P21/c (no. 14), a = 5.806(1), b = 12.923(3), c = 5.628(1) Å, β = 107.49(3)°, V = 402.75(14) Å3, Z = 2; R(F) = 1.42%] and adopts type D in the classification of Fleck et al. (2002b); it is isotypic with the three arsenates brandtite, roselite, zincroselite, and the sulphate kröhnkite. Infinite kröhnkite-type tetrahedral-octahedral chains [(Mg,Co)(AsO4)2(H2O) 2]2- are separated by Ca2+ cations. A very strong hydrogen bond (O⋯O = 2.5294(18) Å) links adjacent chains. Hydrothermally synthesised, orange AgSc(CrO4)2·2H2O is triclinic [space group P1̄ (no. 2), a = 5.586(1), b = 6.054(1), c = 7.432(1) Å, α = 110.74(3), β = 90.21(3), γ = 117.34(3)°, V = 204.56(6) Å3, Z = 1; R(F) = 3.48%] and represents a novel structure type, designated G, among compounds containing kröhnkite-type chains. The structure is metrically pseudo-monoclinic and closely related to those of the monoclinic subtypes F1 (C2/c) and F2 (C2/m). AgSc(CrO4)2·2H2O also represents the first Ag and Sc compound based on a kröhnkite-type chain. The structure is based on infinite tetrahedral-octahedral chains [Sc(CrO4)2(H2O)2] 2- separated by Ag1+ cations. The Ag atom exhibits a [4+4]-coordination, with the AgO8 polyhedron closely resembling a strongly sheared cube. Rb2Cu(Cr2 O7)2·2H2O and isotypic Cs2Cu(Cr2O7)2·2 H2O were both grown at room temperature as orange blades from slightly acidic aqueous solutions. They represent a new, triclinic structure type containing kröhnkite-like octahedral-tetrahedral chains based on bridging Cr2O7 groups [space group P1̄ (no. 2), a = 7.272(1) / 7.462(2), b = 7.648(2) / 7.819(2), c = 7.772(2) / 7.847(2) Å, α = 91.89(3) / 93.19(3), β = 99.72(3) / 99.57(3), γ = 115.79(3) / 116.34(3)°, V = 380.84(15) / 400.23(15) Å3, Z = 1; R(F) = 3.03 / 2.99%]. The Cu atoms show a Jahn-Teller-distorted 'octahedral' coordination environment, approaching an unusual [2+2+2]-coordination. Hydrogen bonding is weak. A distinct positive correlation between the size of the alkali cation and the Cr-O-Cr angle in the few known alkali metal dichromates with kröhnkite-like chains is demonstrated. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: CRYSTAL STRUCTURE; DICHROMATE; KRöHNKITE; TETRAHEDRAL-OCTAHEDRAL CHAIN; WENDWILSONITE